PELATIHAN DAN SEMINAR PEMBERDAYAAN WANITA PELAKU UMKM DI KAWASAN PANTAI BIRU - Nurfatwa Andriani Yasin; Afriyani Afriyani; Asmawiyah Asmawiyah; Muliati Abbas; Nurhidayati Islamiah; Lasty Agustuty; Wisda Zulaeha (Arunika: Jurnal Pengabdian Masyarakat, 2025)
Women micro, small, and medium enterprise (MSME) actors in the Pantai Biru area play a strategic role in supporting household economies and driving the economic development of coastal communities. However, limited knowledge of entrepreneurship, business management, and financial literacy remains a major constraint to business development and sustainability. This Community Service program aims to enhance the entrepreneurial capacity of women MSME actors through entrepreneurship seminars and basic business management training. The implementation methods include interactive lectures, simple case studies, and participatory discussions to encourage active participant engagement. The results indicate an improvement in participants’ understanding of basic entrepreneurial concepts, the importance of financial record-keeping, and awareness of more effective marketing strategies. In addition, the program increases participants’ motivation and self-confidence in managing their businesses independently and sustainably. This activity is expected to serve as an initial step in strengthening women’s economic empowerment and the economic resilience of coastal households in the Pantai Biru area.